Dynamic heterogeneity and non-Gaussian statistics for acetylcholine receptors on live cell membrane - W. He (Nature Portfolio, 2016)
Molecular motion in living cells is known to be more complicated than those determined solely by thermal equilibrium, but a quantitative analysis is still missing. Here, He et al. quantify the lateral motion of proteins on live muscle cell membranes, which doesn’t follow the normal Brownian diffusion.